Original paperEffect of tissue composition on dose distribution in brachytherapy with various photon emitting sources - Ghorbani, Mahdi; Salahshour, Fateme; Haghparast, Abbas; Moghaddas, Toktam Ahmadi; Knaup, Courtney (Journal of Contemporary Brachytherapy, 2014)
Purpose: The aim of this study is to compare the dose in various soft tissues in brachytherapy with photon emitting sources. Material and methods: 103 Pd, 125 I, 169 Yb, 192 Ir brachytherapy sources were simulated with MCNPX Monte Carlo code, and their dose rate constant and radial dose function were compared with the published data. A spherical phantom with 50 cm radius was simulated and the dose at various radial distances in adipose tissue, breast tissue, 4-component soft tissue, brain (grey/white matter), muscle (skeletal), lung tissue, blood (whole), 9-component soft tissue, and water were calculated. The absolute dose and relative dose difference with respect to 9-component soft tissue was obtained for various materials, sources, and distances. Results : There was good agreement between the dosimetric parameters of the sources and the published data. Adipose tissue, breast tissue, 4-component soft tissue, and water showed the greatest difference in dose relative to the dose to the 9-component soft tissue. The other soft tissues showed lower dose differences. The dose difference was also higher for 103 Pd source than for 125 I, 169 Yb, and 192 Ir sources. Furthermore, greater distances from the source had higher relative dose differences and the effect can be justified due to the change in photon spectrum (softening or hardening) as photons traverse the phantom material. Conclusions : The ignorance of soft tissue characteristics (density, composition, etc.) by treatment planning systems incorporates a significant error in dose delivery to the patient in brachytherapy with photon sources. The error depends on the type of soft tissue, brachytherapy source, as well as the distance from the source.